2014
DOI: 10.1101/gr.182238.114
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pol IV/RDR2-dependent transcripts at the genomic scale in Arabidopsis reveals features and regulation of siRNA biogenesis

Abstract: Twenty-four-nucleotide small interfering (si)RNAs are central players in RNA-directed DNA methylation (RdDM), a process that establishes and maintains DNA methylation at transposable elements to ensure genome stability in plants. The plant-specific RNA polymerase IV (Pol IV) is required for siRNA biogenesis and is believed to transcribe RdDM loci to produce primary transcripts that are converted to double-stranded RNAs (dsRNAs) by RDR2 to serve as siRNA precursors. Yet, no such siRNA precursor transcripts have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
193
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(213 citation statements)
references
References 46 publications
(84 reference statements)
17
193
3
Order By: Relevance
“…Since our study did not include a RNA fragmentation step, our sequencing reads should represent the native state of Pol IV-dependent transcripts, and no further assembly of the reads is needed. On the other hand, our results are consistent with the finding of Li et al that P4 RNAs contain a monophosphate in their 5′ end and no poly(A) tail in the 3′ end [32]. The T4 RNA ligase used for our RNAseq library construction requires 5′ monophosphate and 3′ hydroxyl groups of the RNAs.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Since our study did not include a RNA fragmentation step, our sequencing reads should represent the native state of Pol IV-dependent transcripts, and no further assembly of the reads is needed. On the other hand, our results are consistent with the finding of Li et al that P4 RNAs contain a monophosphate in their 5′ end and no poly(A) tail in the 3′ end [32]. The T4 RNA ligase used for our RNAseq library construction requires 5′ monophosphate and 3′ hydroxyl groups of the RNAs.…”
Section: Discussionsupporting
confidence: 83%
“…incorporation of NTPs facilitates release of the transcript, which is then transcribed by RDR2. Of the 4 464 > 24 nt P4 RNA clusters identified in dcl1/2/3/4 mutant plants, we found that 1 751 overlap with DRM2-dependent (D2) loci and 651 overlap with CMT2-dependent (C2) loci, and 73 overlap with both D2 and C2 loci, consistent with the findings that both D2 and C2 loci produce 24-nt siRNAs [13,32]. During the preparation of this manuscript, two independent groups reported short, Pol IV-dependent precursors of 24-nt siRNAs [58,59], which corroborate our results.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations